Sentidos subjetivos na construção do sujeito atingido pelo rompimento da Barragem de Fundão no jornal A Sirene - Santos, Flavia Carolini Pereira dos (2021)
The collapse of the Fundão tailings dam in Mariana caused nineteen deaths and irreversible damage to the environment, devastating the ecosystem and fishing villages. Around forty million cubic meters of tailings dragged houses and plantations from Bento Rodrigues to Espírito Santo, poisoning from Rio Doce to the Atlantic Ocean. In this context, traditional media interferes with mediating the information conveyed about the Fundão dam failure in a “hypocritical scheme”, sometimes supporting the company, sometimes demonizing it (emphasis added). These media also label those affected sometimes as protagonists, sometimes as extras of an eventual disaster. According to Saraiva (2019), these types of media incessantly produce reports, interviews, and information that characterize crime as a simple tragedy. This thesis aims to unveil and analyze the subjective meanings that constitute the subject affected by the collapse of the Fundão dam in the municipality of Mariana-MG, in the regional newspaper “A Sirene”. Qualitative research was chosen to achieve this objective using documentary and bibliographic research to collect and analyze “A Sirene” newspapers. The analysis was performed using Content Analysis. The study of the newspaper “A Sirene” made it possible to understand that it is an alternative media, combining characteristics involving it in a political journalistic agenda and framing news in favor of those affected. In conclusion, the general objective of the research was achieved by exposing who the affected people are, how they describe the collapse of the Fundão tailings dam, and how they mischaracterize the traditional public media to make the “A Sirene” newspaper their primary means of communication. Finally, it is necessary that the “A Sirene” continue to exist so that those affected can have a space for denunciation, a complete dossier to record their memories, and an essential contribution to the struggle to guarantee rights and communication.